Direct visualization of microphase separation in block copoly(3-alkylthiophene)s1. Issue 12 (11th February 2015) - Willot, Pieter; Teyssandier, Joan; Dujardin, Wouter; Adisoejoso, Jinne; De Feyter, Steven; Moerman, David; Leclère, Philippe; Lazzaroni, Roberto; Koeckelberghs, Guy
<x xml:space="preserve">Abstract</x> A copoly(3-alkylthiophene) block copolymer was synthesized in a one-pot block copolymerization reaction, starting from a functional o-tolyl initiator in order to maximize A–B diblock copolymer formation. The microphase separation behaviour was directly visualized using STM.